consumers’ motivations of secondhand exchanges in virtual communities: the case of Idle Fish - He, Han (2017)
Nowadays, more and more people conduct secondhand exchanges and join in virtual communities in China. Alibaba, as a world-famous e-commerce company, has already found this trend and launched an online second-hand goods marketplace called Idle Fish many years ago. This paper reports on a study of motivations why the users of Idle Fish conduct secondhand exchanges and join in Fish Ponds which are small virtual communities on Idle Fish. In this research, 12 online interviews are conducted. All the informants are from four Fish Ponds which have the highest traffic on Idle Fish. In addition, 102 postings, the comments and Q&A on Idle Fish are downloaded and collected. Through thematic analysis of these data, seven types of motivations are found including intrinsic, altruistic, environmental, safety, morality, social connection and instrumental motivations. Then lived experience when the informants join in Fish Ponds and conduct secondhand exchanges on Idle Fish is used to support these motivation. In the end, a muddle of theories of motivations in consumer behavior are used to explain these motivations. Most of the informants mentioned that they feel happy and excited when they buy or sell some secondhand items which can be regarded as the intrinsic motivation of secondhand exchanges on Idle Fish, but the sources of their sense of amusement are totally different. When the users get some help from other members of Fish Ponds, they also want to repay the help to others. The users of Idle Fish also wants to reduce the guilt of wasting their parents’ hard earned money, their own money or limited resources through online secondhand exchanges when they buy and sell something that they don’t need. When the users feel frustrated and helpless, they will seek help and advice from other members of Fish Ponds. Other members’ acceptance, help and kindness will give the users a sense of belonging in that Fish Pond. Moreover, the users conduct secondhand exchanges and join in Fish Ponds on Idle Fish in order to satisfy their basic needs including safety, payments, decreasing burdens, saving space, saving time, increasing convenience and efficiency.